Surface roughness and bond strength between Y-TZP and self-adhesive resin cement after air particle abrasion protocols - De Sousa, Rafael Santiago; Campos, Fernanda; Sarmento, Hugo Ramalho; Alves, Maria Luiza Lima; Dal Piva, Amanda Maria De Oliveira [UNESP]; Gondim, Laísa Daniel; Souza, Rodrigo Othávio Assunção (My University, 2016)
The aim of this study was to evaluate the influence of different air particle abrasion (APA) protocols - with variations in particle types, duration of application, and the distance between the device tip and the ceramic - on the surface roughness (SR) of zirconia-based ceramic (yttria-stabilized tetragonal zirconia polycrystal [Y-TZP]) and the shear bond strength (SBS) between Y-TZP and resin cement. In total, 135 sintered Y-TZP blocks were polished and divided into 9 groups according to 3 factors: particle (alumina vs alumina coated with silica), duration (5 vs 10 seconds), and distance (contact vs 10 mm away). All 3 factors significantly influenced the SR values between the experimental groups and the control group. For SBS, only the particle type was a statistically significant factor. Results showed that air particle abrasion with silica-coated alumina resulted in higher SBS, even though the SR values associated with those groups were not the highest.
Keywords: Adhesion; Air particle abrasion; Y-TZP; Zirconia